Implications of cultural diffusion in Nigeria through the television medium: a survey of selected youths in Imo state - Emetumah, Fatima Ijeoma; Emetumah, Faisal Chinonso (Advances in Social Sciences Research Journal, 2015)
The impact of television on cultural diffusion is not in doubt; technological advancement of the television medium has turned the entire world into a global village. Developed countries influence the less developed ones with their culture through modern information dissemination apparatuses; these cultural influences have both positive and negative impacts on the ethical values of youths in a developing country like Nigeria. The study looks at the cultural implications and influences of television on youth cultural integration. Relevant literature bordering on cultural integration as well as the impact of globalization on culture was reviewed, premised on the ‘cultivation theory’ developed by George Gerbner. Survey method involving the use questionnaires was employed to articulate the extent of media influence on the values and beliefs of purposively selected youths in Imo State, Nigeria. Empirical data from the survey was presented and analysis produced a number of vital findings: television provided a globalization mechanism that encouraged cultural diffusion and migration; television was perceived as an important relaxation tool; television can be employed in improving ethical standards; youths are vulnerable to foreign ideas from satellite and cable television. Conclusively, the study recommends that television should be employed in improving traditional values through indigenous cultural information dissemination and expounding national heritage.